Antenatal education and postnatal support strategies for improving rates of exclusive breast feeding: randomised controlled trial. Issue 7620 (1st August 2007) - Su, Lin-Lin; Chong, Yap-Seng; Chan, Yiong-Huak; Chan, Yah-Shih; Fok, Doris; Tun, Kay-Thwe; Ng, Faith S P; Rauff, Mary
Abstract : Objective To investigate whether antenatal breast feeding education alone or postnatal lactation support alone improves rates of exclusive breast feeding compared with routine hospital care. Design Randomised controlled trial. Setting A tertiary hospital in Singapore. Participants 450 women with uncomplicated pregnancies. Main outcome measures Primary outcomes were rates of exclusive breast feeding at discharge from hospital and two weeks, six weeks, three months, and six months after delivery. Secondary outcomes were rates of any breast feeding. Results Compared with women who received routine care, women in the postnatal support group were more likely to breastfeed exclusively at two weeks (relative risk 1.82, 95% confidence interval 1.14 to 2.90), six weeks (1.85, 1.11 to 3.09), three months (1.87, 1.03 to 3.41), and six months (2.12, 1.03 to 4.37) postnatally. Women receiving antenatal education were more likely to breast feed exclusively at six weeks (1.73, 1.04 to 2.90), three months (1.92, 1.07 to 3.48), and six months (2.16, 1.05 to 4.43) postnatally. The numbers needed to treat to achieve one woman exclusively breast feeding at six months were 11 (6 to 80) for postnatal support and 10 (6 to 60) for antenatal education. Women who received postnatal support were more likely to exclusively or predominantly breast feed two weeks after delivery compared with women who received antenatal education (1.53, 1.01 to 2.31). The rate of any breastfeeding six weeks after delivery was also higher in the postnatal support group compared with women who received routine care (1.16, 1.02 to 1.31). Conclusions Antenatal breast feeding education and postnatal lactation support, as single interventions based in hospital both significantly improve rates of exclusive breast feeding up to six months after delivery. Postnatal support was marginally more effective than antenatal education. Trial registration Clinical Trials NCT00270920 .